(untitled) (Academia Journal of Medicine, 2019)
Background: To describe the neurological manifestations and neuroimaging of heatstroke patients. Subjects and Methods: We extracted data retrospectively from patients’ files and described their neurological manifestations and radiological features. An experienced brain-imaging radiologist reviewed and analyzed patients’ radiographs to report on signs of abnormality. Results: This group included fifteen patients; eight males (53%) and seven females (47%), with an average age of (51.2 ± 10.1) years. Seven patients underwent brain imaging (CT scan), yet abnormal findings were detected in one patient images only. On the initial CT it showed bilateral thalamic and brainstem diffuse hypo densities. The follow-up CT scans showed acute hemorrhage in the pons and 4th ventricle. There was third intra-ventricular extension of blood, with mild hydrocephalus. Conclusion: The study presented non-specific neurological findings that were associated with heatstroke patients. These findings may affect management and potential complications prognosis.